Behaviour of slender concrete-filled dual steel tubular columns subjected to eccentric loads. (January 2021) - Albero, V.; Ibañez, C.; Piquer, A.; Hernández-Figueirido, D.
Abstract: In this paper an experimental program on concrete-filled steel tubular columns subjected to eccentric loads is presented. The columns have different cross-sectional configurations, including single concrete-filled steel tubular columns (CFST) and concrete-filled dual steel tubular columns (CFDST). The response of all the columns was studied and the physical state of all the specimens after the tests was checked. The level of utilisation achieved by each type of column in relation to its cross-sectional resistance was analysed together with the influence of the extra inner tube or the inner filling of concrete for the CFDST specimens. Finally, EN1994-1-1 provisions were assessed by comparing the experimental results with the predictions given by the simplified method which appears to be conservative in this case. Graphical abstract: Unlabelled Image Highligths: Tests on eccentrically loaded slender concrete-filled dual steel tubular columns. Influence of type of section, concrete infill and ductility are studied. Deflection, and longitudinal and transversal strain are analysed Sectional fiber model is developed to obtain M-N curves. Provisions of Eurocode 4 are assessed and compared to experimental data.